Effect of small dose intermittent IV pethidine in combination with diclofenac for post operative pain relief (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background: Post operative pain is an acute type of pain. There is convincing evidence that unrelieved post operative pain may result in harmful physiological and psychological effects with significant morbidity and even mortality. Complete and effective pain management is an essential for the patient who recovers from surgery. For this reason we used easy available drugs opioid, NSAID and its combination for better post operative analgesia with the aim of avoiding expensive patient controlled analgesia technique, infusion or intramuscular painful roout of administration. Methods: 120 patients ASA grade-I and II were selected for post operative pain releive in upper and lower abdominal surgery. All patients divided into three groups and each group are equal in number and same type of surgery. Among the three groups, two groups received small intermittent intravenous pethidine and diclofenac pre and post operatively and other groups received intra muscular pethidine with diclofenac pre and post operatively (controlled group). All vital parameter and pain score both VAS and VRS were recorded in perioperative period up to 24 hours postoperatively. Result: Good level of anaesthesia was achieved in all groups (VAS>30mm) of upper and lower abdominal surgery except early post operative period. In early post operative period significant difference of VAS in group II and III (P